The Role of Smartphone Addiction on Bed Procrastination and Mindful Eating Behavior in Adolescents - Syiffa Azahra Tri Rahayu; Riselligia Caninsti (Universitas Muhammadiyah Surakarta, 2024)
Excessive smartphone use causes the behavior of delaying bedtime and decreasing mindful eating in teenagers. The aim of this research is to find out and explain how much the risk of smartphone addiction plays a role in increasing bed procrastination behavior and decreasing mindful eating in adolescents. There were 192 participants involved in the research with the sampling technique used was convenience sampling. Participant characteristics include teenagers aged 18 – 21 years and have a cut off score for smartphone addiction. Each participant filled out the Smartphone Addiction Scale Short Version for Adolescents, Bedtime Procrastination Scale, and Mindful Eating Questionnaire questionnaires. Data were analyzed using a simple regression method. Based on the results of the regression test, it was found that the risk of smartphone addiction played a 6.1% role in increasing bed procrastination behavior and a 13.3% role in reducing mindful eating behavior. The results of this study also found other factors that play a role in procrastination behavior at bedtime and mindful eating in teenagers besides excessive smartphone use. Therefore, it is hoped that future research will be able to consider and look at other factors besides the risk of smartphone addiction that play a role in bed procrastination and mindful eating.